2004
DOI: 10.1007/s00415-004-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Is transient global amnesia a risk factor for amnestic mild cognitive impairment?

Abstract: Transient Global Amnesia (TGA) is a common condition of unknown aetiology characterised by the abrupt onset of severe anterograde amnesia, which lasts less than 24 hours. Some authors have suggested that subclinical impairment of memory functions may persist for much longer, but neuropsychological assessment lasting years after TGA attack has not been performed so far. The aim of this study was to evaluate longterm cognitive functions in patients with a previous TGA episode. Fifty-five patients underwent a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
4
27
2
5
Order By: Relevance
“…The findings of two additional studies have shown that cognitive deficits may persist after the end of the acute phase of the amnesic episode and be detected 3 to 4 days [9], and more than one year after the episode [4]. However, whether the persisting cognitive deficits result from the episode of TGA or if they are due to a pre-existing condition is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of two additional studies have shown that cognitive deficits may persist after the end of the acute phase of the amnesic episode and be detected 3 to 4 days [9], and more than one year after the episode [4]. However, whether the persisting cognitive deficits result from the episode of TGA or if they are due to a pre-existing condition is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, they should be associated with a higher probability of at least partially persistent cognitive impairment and of a detectable neuronal loss. Whereas numerous investigators have reported such long-lasting neuropsychological deficits [6,7,8,9,10,11], several studies devoted to imaging parameters [12], and especially the few dealing with the time course of the DWI changes, describe a complete remission of the hippocampal lesions without structural sequelae [3,4]. The important question, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10, 14, 20]]. In contrast to our subjects, who were tested at an average of 3 years after the episode, most of the previously reported patients were examined within the first weeks or months after a TGA attack, hence at a period which still might be during the recovery phase.…”
Section: Discussionmentioning
confidence: 81%